Characteristics of biphasic calcium phosphate scaffold formed by Anadara granosa shell synthesis - Rima Parwati Sari; Maharani Dewinta Sari; Andiani Ramanindia; Karimatul Fitri; Michelle Rosalind Susanto; Safira Agnes Pratiwi; Diajeng Ayu Permatasari Yusuf; Widyasri Prananingrum; Vivin Ariestania; Widaningsih; Anindita Apsari; Widyastuti; Arya Brahmanta; Eddy Hermanto (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2026)
Background: Bone augmentation requires biomaterials that can trigger bone regeneration, especially when treating alveolar bone defects. Biphasic calcium phosphate (BCP) can induce cell proliferation and differentiation. Anadara granosa shell can be synthesized into BCP and made into a scaffold with the addition of gelatin. Purpose: To determine the optimal BCP ratio from A. granosa shell synthesis and to establish the material characteristics. Methods: Anadara granosa shells were synthesized using the hydrothermal method at 200°C for 12 and 18 hours, followed by particle size analysis. Next, the resulting powder was made into scaffolds by adding gelatin through the freeze-drying method, and a series of observations were performed regarding its morphology, pore size, porosity, compressive strength (CS), and cell viability. The data were analyzed using an independent t-test, with p < 0.05. Results: Synthesis of A. granosa shells for 12 hours produced a BCP ratio of 69:20 with 11% calcite content and a particle size of 3,343.00 ± 445.25 nm, whereas synthesis for 18 hours produced a ratio of 22:78 with a particle size of 919.96 ± 375.77 nm. In scaffold manufacture, the BCP18 pore size (26.56–145.45) was smaller than that of BCP12 (19.72–309.09), the porosity level was lower (61.49% vs. 81.98%, respectively), and the CS was higher (4.66 ± 1.12 vs. 2.89 ± 0.799, respectively). Nevertheless, both had relatively good cell viability (≥50%). Conclusion: Biphasic calcium phosphate obtained from A. granosa shell synthesis exhibits varying ratios; nevertheless, both variants possess favorable attributes for consideration as potential bone substitute materials, as they meet the necessary biocompatibility requirements.